On the rate of convergence in the local theorem with limiting stable distributions - Banys, J.; Kalinauskaitė, N.; Vaitkus, P. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: И. И. Банис, Н. Б. Калинаускайте, П. С. Вайткус. О скорости сходимости к устойчивым распределениям в локальной теореме J. Banys, N. Kalinauskaitė, P. Vaitkus. Konvergavimo greičio į ribinį stabilų dėsnį lokalinėje teoremoje klausimu